2005
DOI: 10.1002/pi.1848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(1‐hexene)s end‐functionalized with phenols

Abstract: Electrophilic alkylations of phenol/2,6-dimethylphenol were performed with vinylideneterminated poly(1-hexene)s using BF 3 ·OEt 2 catalyst. Vinylidene-terminated poly(1-hexene)s with M n varying from 400 to 10000 were prepared by bulk polymerization of 1-hexene at 50 to −20 • C using Cp 2 ZrCl 2 /MAO catalysts. The phenol/2,6-dimethylphenol-terminated poly(1-hexene)s was characterized by NMR ( 1 H, 13 C), UV, IR and vapor phase osmometer (VPO). The isomer distribution (ortho, para and ortho/para) was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In 2005, Yanjarappaand coworkers synthesized poly(1-hexene)s end-functionalized with phenols [17]. To this end, they produced vinylidene-terminated poly(1-hexene)s by bulk polymerization of 1-hexene at 50 to À20 C using Cp 2 ZrCl 2 /MAO catalyst, and then they incorporated 2,6-dimethylphenol to these unsaturated chains with BF 3 -OEt 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Yanjarappaand coworkers synthesized poly(1-hexene)s end-functionalized with phenols [17]. To this end, they produced vinylidene-terminated poly(1-hexene)s by bulk polymerization of 1-hexene at 50 to À20 C using Cp 2 ZrCl 2 /MAO catalyst, and then they incorporated 2,6-dimethylphenol to these unsaturated chains with BF 3 -OEt 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now, no investigation that reports functionalization of higher α-olefins oligomers to use them in the photo-curable adhesive applications has been reported yet. [27,28] Mirmohammadi and coworkers produced photo-crosslinkable nanohybrids based on poly(ε-caprolactone fumarate)/polyhedral oligomeric silsesquioxane (POSS). [29] Authors reported that the synthesized macromers can be photo-cross-linked by visible light irradiation in the presence of photoinitiator and accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, well-defined functionalized polyolefins and the corresponding polyolefin-derived graft and block copolymers can be produced applying nonradical postpolymerization or catalytic approaches. Based on structural differences, functionalized polyolefins synthesized by catalysis can be divided into several classes, viz. polymers containing randomly distributed functionalized branches, linear polymers containing randomly distributed functional groups directly attached to the polymer backbone, chain-end-functionalized polyolefins, and polyolefin-derived graft and block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Several routes lead to polyolefins bearing a terminal functional group, viz. postreactor modification of for example unsaturated chain-ends, the use of functionalized chain transfer agents or functionalized chain stoppers in combination with chain transfer agents, coordinative chain-transfer polymerization (CCTP) followed by controlled oxidation, or olefin metathesis. Short-chain branched polyolefins containing randomly distributed functionalized branches are typically produced by copolymerization of ethylene and functionalized comonomers. In the case of comonomers containing nucleophilic functionalities, the latter typically have to be pacified to avoid catalyst deactivation unless appropriate late transition metal catalysts are applied. Comonomers containing electrophilic functionalities can be used without protection, but in this case the obtained copolymers have to undergo a postpolymerization oxidation treatment to obtain the desired functionality. Well-defined randomly functionalized PEs, where the functionalities are directly bonded to the main chain, are most effecti...…”
Section: Introductionmentioning
confidence: 99%